Correction of rectal sacculation through lateral resection in dogs with perineal hernia ? Technique description - Moraes, P. C. [UNESP]; Zanetti, N. M. [UNESP]; Burger, C. P. [UNESP]; Meirelles, A. E W B [UNESP]; Canola, J. C. [UNESP]; Isola, J. G M P [UNESP] (FapUNIFESP (SciELO), 2013)
The occurrence of perineal hernias in dogs during routine clinical surgery is frequent. The coexistence of rectal diseases that go undiagnosed or are not correctly treated can cause recurrence and postoperative complications. The objective of this report is to describe a surgical technique for treatment of rectal sacculation through lateral resection in dogs with perineal hernia, whereby restoring the rectal integrity.
Keywords: dog; Perineal hernia; Rectal disease